1990
DOI: 10.1182/blood.v76.11.2303.bloodjournal76112303
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interleukin-6 during human immunodeficiency virus infection

Abstract: Interleukin-6 (IL-6), a multifunctional cytokine produced in monocytes, fibroblasts, and other cell types, is induced by a variety of stimuli, including bacteria, viruses, and other cytokines. When normal monocyte cultures were exposed to a monocytotropic strain of human immunodeficiency virus (HIV), HTLV-IIIBa-L, significant levels of IL-6 bioactivity were detected in the culture supernatants after 12 to 43 days of incubation, at a time when there was associated evidence of HIV production. Similarly, when nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The functional capacity of these ceils was assessed indirectly by comparing their number with plasma 1L-6 levels. The IL-6 levels were higher than normal in the HIV patients, in keeping with a previous report [26], but the IL-6 level did not correlate with CDC category or total serum IgG level as reported elsewhere [27]. However, the plasma IL-6 level did correlate with the number of monocytes with the larger, activated phenotype.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The functional capacity of these ceils was assessed indirectly by comparing their number with plasma 1L-6 levels. The IL-6 levels were higher than normal in the HIV patients, in keeping with a previous report [26], but the IL-6 level did not correlate with CDC category or total serum IgG level as reported elsewhere [27]. However, the plasma IL-6 level did correlate with the number of monocytes with the larger, activated phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…HIV infected monocytes had decreased microbicidal activity in some reports [20,21] but other workers found no such abnormalities [22][23][24]. Similarly, cytokine secretion has been reported to be either abnormal [25][26][27] or normal [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, IL-6, IL-4 and TNF-a were considered to induce B cell hyperactivity [8,22,23]. Some authors have ascribed the hypergammaglobulinaemia of HIV-1-infected individuals to an increased production of IL-6 by cells of the monocyte-macrophage system as a consequence of HIV-1 infection [22,24]. Nevertheless, hypergammaglobulinaemia in HIV-1-infected persons does not clearly correlate with plasma levels of IL-6 [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have demonstrated that phagocytosis of M. tuberculosis induces macrophage activation, and production of proinflammatory cytokines, namely TNF-a, IL-1b and IL-6 by macrophages, is known to enhance replication of HIV-1 (Molina et al, 1989;Weiss et al, 1989;Birx et al, 1990;Emilie et al, 1990;Lafeuillade et al, 1991;Herbein & Varin, 2010;Cozzi-Lepri et al, 2011). Growth of M. tuberculosis was observed to be significantly greater in HIV-1-infected monocyte-derived macrophages (MDMs) compared with that in HIV-1-negative cells (Imperiali et al, 2001).…”
Section: Reciprocal Effects Of Hiv/m Tuberculosis On Each Othermentioning
confidence: 99%